Flight Data Recorder: Always-on Tracing and Scalable Analysis of Persistent State Interactions to Improve Systems and Security Management - Kiciman, Emre; Daniels, Brad; Kumar, Arunvijay; Wang, Yi-Min; Roussev, Roussi; Lu, Shan; Lee, Juhan; Verbowski, Chad (The 7th USENIX Symposium on Operating Systems Design and Implementation (OSDI '06), 2006)
Mismanagement of the persistent state of a system—all the executable files, configuration settings and other data that govern how a system functions—causes reliability problems, security vulnerabilities, and drives up operation costs. Recent research traces persistent state interactions—how state is read, modified, etc.—to help troubleshooting, change management and malware mitigation, but has been limited by the difficulty of collecting, storing, and analyzing the 10s to 100s of millions of daily events that occur on a single machine, much less the 1000s or more machines in many computing environments. We present the Flight Data Recorder (FDR) that enables always-on tracing, storage and analysis of persistent state interactions. FDR uses a domain-specific log format, tailored to observed file system workloads and common systems management queries. Our lossless log format compresses logs to only 0.5-0.9 bytes per interaction. In this log format, 1000 machine-days of logs—over 25 billion events—can be analyzed in less than 30 minutes. We report on our deployment of FDR to 207 production machines at MSN, and show that a single centralized collection machine can potentially scale to collecting and analyzing the complete records of persistent state interactions from 4000+ machines. Furthermore, our tracing technology is shipping as part of the Windows Vista OS.